2D ЎЛЧАМЛИ p-n-ЎТИШ ФОТОТОКЛАРИ ВА ДИФФЕРЕНЦИАЛ ЎТКАЗУВЧАНЛИГИ - Гулямов, Г.; Дадамирзаев, М.Ғ.; Қосимова, М.О. (SCIENCE and SOCIETY, 2022)
The dependence of the current-voltage characteristic is theoretically investigated of a two-dimensional p-n junction on the wavelength of light. The results obtained were compared with the experimental results. Theoretically, it has been shown that the two-dimensional differential conductivity of the p-n junction is greater than the three-dimensional differential conductivity of the p-n junction